PELATIHAN MICROSOFT OFFICE UNTUK MENINGKATKAN KOMPETENSI GURU DI DESA MEKONG - Sri Gemawati; Musraini, M; Rike Marjulisa; Ayunda Putri; Irsan Taufik Ali (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Microsoft Office training for teachers in Mekong Village, West Tebing Tinggi District, aims to enhance teachers' technical competence in using software that is essential for the modern educational process. Skills in Microsoft Word, Excel, and PowerPoint are expected to help teachers optimize the learning process, prepare teaching materials, and carry out administrative tasks more effectively. This training is highly relevant, especially for teachers in remote areas where the use of technology is often limited but very much needed to support more interactive learning and better-organized administration. The training is conducted face-to-face with a combination of lectures and hands-on practice, designed to ensure participants can understand and apply the material well. The training is conducted face-to-face with a combination of lectures and hands-on practice, designed to ensure participants can understand and apply the material well. Teachers are trained in the use of important Microsoft Office features, such as creating mass mailings using mail merge in Word, analyzing student grade data in Excel with formulas like IF, VLOOKUP, and HLOOKUP, and creating interactive presentations in PowerPoint. With this method, the transfer of knowledge and skills occurs optimally, and participants can immediately apply the knowledge they have gained in the context of their daily work. The evaluation of the training results shows a significant improvement in participants' competencies, with an average increase of 25% based on pre-test and post-test results. In conclusion, face-to-face Microsoft Office training has proven effective in enhancing teachers' technical skills. For further development, it is recommended to have advanced training with a longer duration and more in-depth material, so that teachers are better prepared to face technological challenges in the world of education.